Capital structure and profitability of the banking sector that operates in Peru - Ramírez Huerta, Valiente Pantaleón (2021)
Objective: Establish the association of the weighted average cost of capital with the return on assets, of the alternative cost of capital with the return on equity, and of the average cost of debt with the return on sales in banks operating in Peru. Method: The investigation had a quantitative approach, was non-experimental transversal, and correlational.  The population consisted of 18 banks, and it was not necessary to calculate the sample. The data was collected through the documentary analysis of the annual financial statements from 2010 to 2018 of each bank; the hypotheses were tested using the correlation index. Results: The weighted average cost of capital, equity capital, and debt capital were determined; as well as the index of return on assets, on net worth, on sales, and on the added economic value. Conclusion: There is an inverse correlation between the weighted average cost of capital and the return on assets; also, between the cost of debt net of tax shield and the return on sales; however, there is a direct correlation between the alternative cost of capital and the return on equity.